The Importance of Relationship Management in GCC Region - Kapasi, Anshul; Kurian, Dias Joseph; Ayrancioglu, Oguz (2012)
ABSTRACT This document is divided in several parts. In the first section, we would look at the GCC region and conduct a PEST analysis for the individual countries in the region that currently constitute the GCC, along with our perspective on the results that we have obtained. In the second section, we will analyse the history, importance, general advantages, and the current need for railways in the region. We will also combine the data obtained from the first section with the data in the second section and present the scenarios for the region in the near future. In the third section, we will analyse the various aspects of the GCC economies and highlight their inherent dimensions in relation to rail infrastructure projects. In the fourth section, we will detail the current and future business opportunities that BBR can expect to explore in the region, and we would also list the overall rail infrastructure projects that we think would be of interest to BBR. Having done that, we will then analyse, from a theoretical perspective, the critical stages that organisations usually should go through in order to establish their presence in any region and the implications for them. And finally, we will give an in-depth analysis of the most important part of the exercise; the development of WASTA or the unique regional relationships that bind their society, culture, and also business. We will explain why BBR needs to understand, accept, emulate, and develop WASTA. We will then analyse the pertinent implications that our research delivers and use it in a innovative manner to suggest business development models through strategies, while justifying our perspectives on the theoretical expositions that we had previously detailed. Here we will firstly, explain the implication for leadership attributes that are relevant in the GCC region. Secondly we will explore how to convert BBR’s available competencies and the inherent need of the region into an advantageous Blue Ocean Strategy and finally, we will explain the implications for forming strategic alliances in the region. Having detailed the implications we will include our research on the socio-cultural and communications dimensions of the region Last but not least, we will provide another 20-30 year scenario for the region, which showcases the unique elements that are under play in the region, which we believe will help the region develop into the most powerful economy in the world. Through this, we will try and establish critical reasons why BBR as an organisation should plan, not just for being present in the region for the medium term, but also get ready for the longest haul. In the Annexure part, we have provided detailed explanations of the relevant theory, interviews, miscellaneous data on the reports, and the original article on WASTA (Hutchings and Weir, 2006)(with permissions) that we used above. With this report, we hope that our work will come handy during BBR’s journey into the Arab World.